Peningkatan Motivasi dan Hasil Belajar IPS melalui Model Group Investigation di Kelas IV Sekolah Dasar - Sri Zuhana Idayatun; Esti Setiawati (UM Purwokerto Press, 2022)
This study aims to increase motivation and learning outcomes of SDA material for social studies subject matter through the Group Investigation (GI) model. The research subjects were fourth-grade students at SDN Kemadang for the 2018/2019 academic year, totaling 20 students. The method used is Classroom Action Research which consists of two cycles. Every cycle consists of four steps, namely planning, action, observation, and reflection. Collect data using observation sheets of learning motivation and student learning outcomes tests. The result showed that the Group Investigation (GI) model could increase the motivation and learning outcomes of the fourth-grade students at SDN Kemadang. It shows the increase in students' motivation and learning outcomes. In the first cycle, the learning motivation reached 72.5% in a good enough category in the second cycle is increased to 80% with the best type. Completeness of learning outcomes in the first cycle reached 55%, with an average score of 76.10 in enough category, and the end of the second cycle increased to 80% with an average score of 82.05 in the best category.